Genetic and enzymatic characterisation of wood degrading strains of Phanerochaete species - De Koker, T. H. (Theodorus Hermanus), 1965- (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2000.